Aikamme kasvatus: vain muutos on pysyvää? 14 eläytymismenetelmätutkimusta - Eskola, Jari; Nikanto, Ilona; Virtanen, Satu (Tampere University Press, 2018)
"This compilation introduces 14 articles that use method of empathy-based stories as a methodology and all of which look at changes in the field of education. This compilation discusses many current themes, such as changes in teaching and working methods at different levels of education, change management and curriculum work. The book also provides an insight into how children experience stories of news reports or how girls construct girlhood in their stories. All the articles in this compilation are combined with a review of educational change, along with a methodological connection: the material of all the articles is collected using the method of empathy-based stories. The book shows how multipurpose this method is: it is equally suitable for examining the perceptions of children as well as for examining a whole organizational change. The book presents not only the practical research carried out with the method, but also provides a guide to the methodology and introduces good practices. "